Integrin inhibition differentially remodels vascular networks in lung metastases driven by vessel co-option or angiogenesis - Laura Marcos-Zazo; Iván Carrera-Aguado; Jesús Gómez-Escudero; Patricia Berlana-Galán; Irene Torre-Cea; Elena Guerra-Paes; Celia Redondo-Gonzalez; Juan Sánchez-Mateos; Daniel Cáceres-Calle; Óscar Maiques; Miguel Pericacho; Susana Fraile; et al. (Angiogenesis, 2026)
Tumor progression depends on an adequate blood supply to sustain oxygen and nutrients delivery. While tumor angiogenesis involves the formation of new blood vessels from pre-existing ones, vessel co-option represents a non-angiogenic vascularization strategy whereby tumor cells utilize pre-existing host vessels. Co-opted vessels have been considered refractory to anti-angiogenic therapies, and pharmacological modulation of co-opted vessels remains limited. In this study, we investigate the effects of low-dose cilengitide on tumor vascular remodeling in vessel co-option and angiogenic metastatic models. Our results reveal that cilengitide exerts distinct vascular effects depending on the mode of tumor vascularization. In vessel co-option-driven tumors, cilengitide treatment is associated with the remodeling of the co-opted vasculature into a more organized normalized vascular network, characterized by an increased number of functional blood vessels and enhanced vascular barrier integrity. In contrast, in angiogenic-driven tumors, cilengitide treatment promotes an expansion of the vascular network consistent with augmented, but structurally immature angiogenesis. Importantly, vascular remodeling in vessel co-option metastases is accompanied by enhanced blood vessel perfusion and reduced hypoxia, which correlates with enhanced responsiveness to chemotherapy. Conversely, in angiogenic metastases, the vascular network induced by low-dose cilengitide fails to support immunocompetent microenvironmental features and is associated with increased chemotherapy resistance. This study provides the first evidence that co-opted vasculature can be therapeutically targeted via integrin inhibition, suggesting vascular normalization remodeling as a potential strategy to overcome resistance in tumors undergoing vessel co-option.

Electrochemical oxidation of multi-drug traces in synthetic fresh urine using BDD and DSA (Ti/IrO2) anodes - Raul José Alves Felisardo; Gabriel A. Cerrón-Calle; Marcos Roberto de Vasconcelos Lanza; Eliane Bezerra Cavalcanti; Sergi Garcia-Segura (Journal of Environmental Chemical Engineering, 2025)

Electrochemical persulfate activation for degradation of BPA using a novel self-standing CuOx/CoOx cathode - Gabriel Antonio Cerrón-Calle; Marco Flores; Manuel A. Roldan; Kenneth Flores; Enric Brillas; Alexsandro J. dos Santos; Sergi Garcia-Segura (Chemical Engineering Journal, 2025)

Population Dynamics of the Crocodile Shark, Pseudocarcharias kamoharai, in the Tropical Equatorial Pacific Ocean, Ecuador - Marcos Calle-Morán; Eugenio Aragón-Noriega; Ana Hernández-Téllez; Emigdio Marín-Enríquez; Javier Tovar-Ávila; Juan Arzola-González; Jorge Payán-Alejo (Fishes, 2024)
The objectives of this study were to determine the rates of natural mortality (M), fishing mortality (F), total mortality (Z), the exploitation rates (E), as well as the biological reference points (BRPs) and the annual removal rates (R) of the crocodile shark, Pseudocarcharias kamoharai, in the Ecuadorian Pacific. Thirty similar and different models were applied to determine all these rates. These equations were obtained from studies on teleost and chondrichthyan fish. The biological parameters, including age, growth, longevity, and reproduction, were obtained from the specialized literature based on the biology of P. kamoharai in Ecuadorian waters. These biological parameters were used in all the models considered here. The M estimations were 0.14 to 0.28 based on six models for chondrichthyans and osteichthyes. These values were similar to the six algorithms designed for cartilaginous fish, ranging from 0.16 to 0.35; for this reason, these mortality rates were considered low. The Z values ranged from 0.08 to 0.51; however, they were not considered given that the three estimations were less than M, and only the Z = 0.51 was considered. Given that Z = 0.51 and M = 0.24, an F = 0.27 was obtained by subtraction, indicating a low mortality by fishing. E had values between 0.21 and 0.53, which indicated overexploitation that exceeded the Eopt = 0.50 value. The obtained BRPs were Fopt = 0.10 and 0.12 and Flim = 0.16, which showed that the optimal fishing levels (best possible capture) to achieve long-term sustainable exploitation of the stock encompass 10 to 16% of the fishing effort applied for this species. However, the F surpassed this prudential range. The annual removal percentage (R = 21%) demonstrated that 21% of the population was being removed. Based on the biology and ecology of this species, all models applied in this study showed that P. kamoharai had low natural and fishing mortality rates and moderate total mortality; its exploitation rate exceeded the fishing limits. These values and their life history traits indicated that this shark species cannot tolerate any fishing level without threatening its populations.

Feeding ecology of the Patagonian toothfish, Dissostichus eleginoides , in Ecuadorian waters - Alfredo Ordiano‐Flores; Katherine E. Méndez Gudiño; Marcos D. Calle‐Morán; Ana R. Hernández‐Téllez; Jacqueline M. Cajas‐Flores (Marine Ecology, 2024)
The Patagonian toothfish or Chilean sea bass, Dissostichus eleginoides , is an ecological and commercially important species captured by the Equatorian fleet in the Southeast Pacific Ocean. This study aimed to determine this species' diet composition and feeding habits captured in three geographical zones from Ecuador during 2017 and 2018. The total length and corporal mass were measured during this period, and the sex and sexual maturity states were determined from 328 individuals. A hypoallometric growth was evidenced by the size‐weight relationship in D. eleginoides , with an allometry coefficient b = 2.34, suggesting that it increases in size more than in weight. The stomach content analysis expressed as the Prey Specific Index of Relative Importance (PSIRI) indicated that D. eleginoides mainly feeds on teleost fish (88.2%) and less on cephalopods (9%) and crustaceans (2.8%). Males and females evidenced a similar diet; however, adults consumed more teleost fish than juveniles. The trophic position ⁓ 4 indicates that the Patagonian toothfish is a secondary carnivore predator with a wide geographic and diet variation related to prey availability. This is the first study regarding the trophic ecology of D. eleginoides in Ecuador, as other studies are lacking. Understanding nutrient and energy flows in ecosystems is crucial for effective fishing management with an ecosystemic approach.

Age and growth of the crocodile shark, Pseudocarcharias kamoharai , in the Eastern Tropical Pacific Ocean - Marcos D. Calle-Morán; E. Alberto Aragón-Noriega; Felipe Galván-Magaña (Marine Biology Research, 2024)

Reproductive biology of the crocodile shark, Pseudocarcharias kamoharai, in the Ecuadorian Pacific Ocean - Marcos D. Calle-Morán; E. Alberto Aragón-Noriega (Regional Studies in Marine Science, 2023)

Trophic chain of the pelagic thresher, Alopias pelagicus, in the Southeastern Pacific Ocean: An approach through stable isotopes of carbon and nitrogen - Marcos D. Calle-Morán; Peggy J. Loor-Andrade; Felipe Galván-Magaña (Food Webs, 2023)

Electrified technologies for physical separation of arsenic from water - Gabriel Antonio Cerrón-Calle; Alexsandro J. dos Santos; Marcos R.V. Lanza; Ming-Chun Lu; Sergi Garcia-Segura (Current Opinion in Environmental Science & Health, 2023)

Reproductive biology of the bigeye thresher, Alopias superciliosus, in the Tropical Eastern Pacific Ocean - Marcos D. Calle-Morán; Magaly P. Fogacho-Guingla; Ana R. Hernández-Téllez; Felipe Galván-Magaña (Regional Studies in Marine Science, 2023)

Size structure, length-body mass relationship, and relative condition factor of the crocodile shark, Pseudocarcharias kamoharai, in the Southeastern Pacific Ocean, Ecuador - Marcos D. Calle-Morán; Maria Cristina Oddone; J. Fernando Márquez-Farías; Ramón Bonfil (Regional Studies in Marine Science, 2023)

Mercury and Cadmium Concentrations in Muscle Tissue of the Blue Shark (Prionace glauca) in the Central Eastern Pacific Ocean - Rubén D. Castro-Rendón; Marcos D. Calle-Morán; Isabel García-Arévalo; Alfredo Ordiano-Flores; Felipe Galván-Magaña (Biological Trace Element Research, 2022)

Diet composition and feeding habits of the crocodile shark, Pseudocarcharias kamoharai - Marcos D. Calle-Morán; Ana R. Hernández-Téllez; Evelyn R. Tibán-Vivar; Yari E. Intriago-Vera; Israel G. Del Valle-Coello; Beatriz C. Loor-Jama; Ángel R. Ganchozo-López (Environmental Biology of Fishes, 2022)

Atlantic salmon in regulated rivers: Understanding river management through the ecosystem services lens - Johan Watz; David Aldvén; Patrik Andreasson; Khadija Aziz; Marco Blixt; Olle Calles; Kristine Lund Bjørnås; Ivan Olsson; Martin Österling; Sanna Stålhammar; Johan Tielman; John J. Piccolo (Fish and Fisheries, 2022)
Known as the “king of fishes,” the Atlantic salmon ( Salmo salar , Salmonidae) is an iconic freshwater species whose contribution to human well‐being has long been recognized, as have widespread declines in its abundance, partly due to river regulation. To understand how salmon conservation has been addressed within the ecosystem services (ES) framework, we synthesized the peer‐reviewed literature on ES provided by salmon in regulated rivers. We developed a search string to capture allusions to provisioning, regulating, supporting and cultural ES and assessed the results to identify knowledge gaps. The effects of hydropower on fisheries catches and on modelled populations were shown in several publications. Overall, few studies focused explicitly on ES from salmon and hydropower; this is surprising given the considerable body of literature on salmon in regulated rivers. Wild salmon as a food source and other provisioning services are less important today than historically. Because predators such as salmon are important for facilitating biodiversity by cycling nutrients and controlling food webs, there is a scope of work for future assessments of these regulating and supporting services. Few papers explicitly addressed cultural ES, despite the salmon's longstanding iconic status; this is a knowledge gap for future ES assessments in relation to hydropower. The influence of ES assessments for policy makers is growing through the Intergovernmental Panel for Biodiversity and Ecosystem Services (IPBES) and the post‐2020 biodiversity strategy. Explicitly addressing ES poses an opportunity for river managers to raise awareness of aquatic conservation efforts and well‐informed decision‐making for sustaining ES.

Latitudinal patterns of species diversity on South American rocky shores: Local processes lead to contrasting trends in regional and local species diversity - Juan J. Cruz‐Motta; Patricia Miloslavich; Edlin Guerra‐Castro; Alejandra Hernández‐Agreda; Cesar Herrera; Francisco Barros; Sergio A. Navarrete; Roger D. Sepúlveda; Tim M. Glasby; Gregorio Bigatti; Maritza Cardenas‐Calle; Pedro B. M. Carneiro; et al. (Journal of Biogeography, 2020)
Aim We evaluated whether patterns of species diversity (α, β and γ) of rocky shore assemblages followed latitudinal gradients (i.e. LDGs) along the South American coasts, and tested hypotheses related to potential processes sustaining or disrupting the expected LDG pattern at various spatial scales. Location Coasts of South America. Taxon Macroalgae and sessile/slow‐moving macrofauna on intertidal rocky shores. Methods We evaluated changes in species composition across 143 sites. The degree of replacement and loss of species at different spatial scales (i.e. coasts, regions and sites) were estimated to help distinguish among ecological, historical and evolutionary hypotheses for explaining LDGs. Furthermore, components of diversity and taxonomic distinctness were measured, and variability in these measures was decomposed using analysis of covariance. Finally, we examined relationships between diversity and a suite of environmental and anthropogenic variables to identify potential mechanisms that may be responsible for the reported spatial relationships. Results Species composition varied with latitude, and this variability was relatively consistent on both coasts. At all spatial scales, replacement of species was the dominant phenomenon (>95%), rather than loss in the total number of species ( Main conclusions Species diversity of South American rocky shores followed, with interruptions, LDGs. The trend of those LDGs, however, depended on the scale and metric used to describe diversity. It is proposed that patterns of LDGs at various scales are not the result of a single overarching process but are strongly influenced by local and regional processes. Although the most evident environmental gradient was the decrease in SST towards the south, it was demonstrated that regional and local environmental variables were also important for understanding the increase in regional β‐diversity towards the tropics.

Solubilization of phosphorus from phosphate rocks with Acidithiobacillus thiooxidans following a growing-then-recovery process - Susana M. Calle-Castañeda; Marco A. Márquez-Godoy; Juan P. Hernández-Ortiz (World Journal of Microbiology and Biotechnology, 2018)

Identifying, attributing, and overcoming common data quality issues of manned station observations - Stefan Hunziker; Stefanie Gubler; Juan Calle; Isabel Moreno; Marcos Andrade; Fernando Velarde; Laura Ticona; Gualberto Carrasco; Yaruska Castellón; Clara Oria; Mischa Croci‐Maspoli; Thomas Konzelmann; et al. (International Journal of Climatology, 2017)
In situ climatological observations are essential for studies related to climate trends and extreme events. However, in many regions of the globe, observational records are affected by a large number of data quality issues. Assessing and controlling the quality of such datasets is an important, often overlooked aspect of climate research. Besides analysing the measurement data, metadata are important for a comprehensive data quality assessment. However, metadata are often missing, but may partly be reconstructed by suitable actions such as station inspections. This study identifies and attributes the most important common data quality issues in Bolivian and Peruvian temperature and precipitation datasets. The same or similar errors are found in many other predominantly manned station networks worldwide. A large fraction of these issues can be traced back to measurement errors by the observers. Therefore, the most effective way to prevent errors is to strengthen the training of observers and to establish a near real‐time quality control ( QC ) procedure. Many common data quality issues are hardly detected by usual QC approaches. Data visualization, however, is an effective tool to identify and attribute those issues, and therefore enables data users to potentially correct errors and to decide which purposes are not affected by specific problems. The resulting increase in usable station records is particularly important in areas where station networks are sparse. In such networks, adequate selection and treatment of time series based on a comprehensive QC procedure may contribute to improving data homogeneity more than statistical data homogenization methods.

Community-onset bacteraemia of unknown origin: clinical characteristics, epidemiology and outcome - C. Hernandez; N. Cobos-Trigueros; C. Feher; L. Morata; C. De La Calle; F. Marco; M. Almela; A. Soriano; J. Mensa; A. Del Rio; J. A. Martinez (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Variability of hair coat and skin traits as related to adaptation in Criollo Limonero cattle - Antonio Landaeta-Hernández; Sunny Zambrano-Nava; Juan P. Hernández-Fonseca; Rosario Godoy; Marcos Calles; José L. Iragorri; Lauderys Añez; Miguel Polanco; Merilio Montero-Urdaneta; Tim Olson (Tropical Animal Health and Production, 2011)